Oral health status and knowledge among 10-15years old type 1 diabetes mellitus children and adolescents in Bengaluru - S Geetha; M Pramila; Kittu Jain; C M Suresh (Wolters Kluwer Medknow Publications, 2019)
Context: Type 1 diabetes mellitus (T1DM) is a chronic systemic metabolic disease. This disorder affects mainly children and adolescents. The main complications of diabetes mellitus affect the organs and tissues rich in capillary vessels such as kidney, retina, and nerves. These complications are secondary to the development of microangiopathy. Similar changes in small vessels can be found in the oral tissues. There is a significant increase in gingival inflammation and plaque seen in children with T1DM. Aims: The aim of this study is to assess the oral health status and knowledge among T1DM children and young adolescents aged 10-15 years in Bengaluru. Subjects and Methods: One hundred and seventy-five 10-15 year-old children with T1DM and 175 age, sex, and socioeconomic status matched nondiabetic controls were included in the study. Oral health status was assessed using community periodontal Index and decayed/decayed-missing/missing-filled/filled teeth index (DMFT/dmft). Oral health knowledge was assessed using 11 item questionnaire. Chi-square test and Student's t-test were used in the statistical analysis. Results: With regard to periodontal status, subjects with healthy periodontal tissue were less in diabetic than control group. Patients with bleeding and calculus were more in diabetic group than control group. The difference between diabetic group and control group was statistically significant (P = 0.001).The mean number of DMFT/dmft were less in diabetics (0.07 ± 0.006)/(0.26 ± 0.05) compared to control groups (0.1 ± 0.01)/(0.84 ± 0.2), respectively. Overall, oral health knowledge was more among diabetic patients (8.3 ± 1.7) compared to controls (7.5 ± 1.8). Conclusions: The results of the present study showed more gingival changes and higher oral health knowledge in diabetic group when compared to control group.